The role of Apolipoprotein E4 on cognitive impairment in Parkinson’s disease and Parkinsonisms - Rosal, Angenelle Eve; Martin, Sarah L.; Strafella, Antonio P. (Frontiers in Neuroscience, 2025)
Cognitive impairment is a prevalent non-motor symptom of Parkinson’s disease (PD), increasing the risk of dementia as the disease progresses. Despite its clinical significance, the etiology of cognitive impairment in PD remains unclear. Apolipoprotein E4 (APOE4), a well-known genetic risk factor of Alzheimer’s disease, has been studied for its potential role in PD-related cognitive impairment. However, findings have been conflicting and thus inconclusive, highlighting a need to critically evaluate the current research. Several studies using neuroimaging modalities have explored the brains of individuals with PD and atypical parkinsonian disorders who have APOE4. Some of these studies have identified distinct neuropathological changes that have been previously reported to be associated with cognitive impairments in those with Parkinsonisms. Here, we review the role of APOE4 on cognitive impairment in PD and atypical Parkinsonisms using neuroimaging evidence. We will examine how APOE4 may contribute to pathological changes within the brain and its association with cognitive impairment.